Lateral Ventricular Volume Asymmetry and Optic Nerve Sheath Diameter Predict Intracranial Pressure in Traumatic Brain Injury Patients - Yang Wang; Ziming Yuan; Zuoyan Zhang; Jiawei Shang; Mingna Li; Wei Wang (Applied Bionics and Biomechanics)
Background. Various noninvasive methods of intracranial pressure (ICP) measurement have been proposed. Each has unique advantages and limitations. This study was aimed at investigating the relationships between lateral ventricular asymmetry on admission computed tomography, optic nerve sheath diameter (ONSD), and ICP in traumatic brain injury (TBI) patients. Methods. A prospective observational study was conducted in the patients admitted to our department between October 2018 and October 2020. 20 patients with moderate-severe TBI with a Glasgow Coma Scale of 3–12 were enrolled. Lateral ventricle volume (LVV) value measurements were conducted using ITK-SNAP software. The lateral ventricular volume ratio (LVR) was quantified by dividing the larger LVV by the smaller. Results. ONSD and LVR had a good correlation with ICP. Admission LVR of >1.735 was shown to have a sensitivity of 90.9% and a specificity of 88.9% for prediction of ICP increase (AUC=0.879; standard error=0.091; 95% CI=0.701 to 1.0; significance level p<0.004). Admission ONSD of >5.55 mm was shown to have a sensitivity of 81.8% and a specificity of 88.9% for prediction of ICP increase (AUC=0.919; standard error=0.062; 95% CI=0.798 to 1.0; significance level p<0.002). Combining the ONSD and LVR, the sensitivity could be improved to 90.9% in parallel test, and the specificity could be improved to 100% in serial test. Conclusion. ONSD and LVR measurements can diagnose elevated ICP in traumatic brain injury patients. ONSD combining with LVR may further improve the diagnostic evaluation.